Simultaneous diffusion, adsorption, and reaction in fluid catalytic cracking catalysts - Bidabehere, Claudia María (2001)
Simultaneous diffusion, adsorption, and reaction that take place inside the zeolitic component of equilibrium commercial fluid catalytic cracking (FCC) catalysts were described by means of heterogeneous models. n-Hexadecane was used as a test reactant at high temperatures (440-550°C) over two different equilibrium catalysts under very short contact times up to 10 s in a Riser Simulator reactor. The system's parameters were obtained by fitting the model to the reactant's gas-phase concentration versus reaction time data. When zeolite intracrystalline diffusion was first assumed as the controlling mechanism for mass transfer, its energy of activation resulted close to the heat of adsorption, suggesting that diffusion in the zeolite micropores could be indeed controlling. The solution under this new approach led to the obtention of parameters that were consistent with the existence of strong diffusion limitations for the reaction and with lower activity in the low unit cell size catalyst. Diffusion, which would be a nonactivated process, had coefficients that were essentially the same in both catalysts, while the energies of activation of the reaction were different and reflected the higher relative importance of the mechanism of monomolecular cracking in the more dealuminated catalyst. The need for a careful assessment of adsorption parameters in FCC catalysts was confirmed by the fact that their magnitudes change significantly as a function of temperature, with adsorption being somewhat stronger on the higher unit cell size catalyst in the temperature range of interest for FCC. The method employed proved to be adequate and sensitive for the quantification of these issues, which are important in reactor design and simulation and catalyst evaluation procedures.